A novel approach to prepare solvent-free cerium dioxide nanofluids. (19th May 2019) - Li, Yun; Yin, Xianze; Weng, Puxin; Zhang, Ming; Wang, Luoxin; Wang, Hua
ABSTRACT: This paper develops a novel approach to prepare solvent-free cerium dioxide (CeO2 ) nanofluids through N, N -didecyl- N -methyl- N -(3-trimethoxysilylpropyl) ammonium chloride covalently grafted on the surface of CeO2 nanoparticles as core, and then poly(ethylene glycol) 4-nonylpheny 13-sulfopropyl ether sodium salt was grafted on the surface of CeO2 nanoparticles through ion exchange reaction. It is obviously observed that CeO2 nanofluids exhibited a solid state at room temperature, whereas they behave as liquid-like when being heated to above 45°C. To detect the properties of CeO2 nanofluids, the morphology, thermal stability, dispersibility, and rheological behavior of CeO2 nanofluids are mainly investigated. It is found that CeO2 nanofluids can flow without solvent existence. Meantime, it shows good dispersion and stability in water and other organic solvents for weeks due to amphiphilic properties of the modifier molecules.